Enlightenment movement of jadids in Khiva khanate - Kayumov, Marufjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article is devoted to the efforts to reform the educational system in the Khiva Khanate at the end of the 19th century and the beginning of the 20th century. In it, the state of the existing education system in the khanate in this period, the influence of the Jadidism movement on the Khiva khanate, which was widespread in Turkestan, are highlighted on the basis of various historical works and archival sources. Based on the data, the actions of representatives of the Jadidism movement in the Khanate, the attitude of the existing government, as well as the representatives of ancient (old traditional) education and religious scholars to the reforms in the field of education and the attitude of the representatives of Jadidism were analyzed.